Effectiveness of Police Press Release Presentation on Journalists' Information Satisfaction - Fatiin, Mufhida; Sonni, Alem Febri; Saeni, Rahman (Palakka : Media and Islamic Communication, 2025)
Effective communication between public institutions and the media fosters transparency, accountability, and trust. However, limited empirical research has explored how press releases' structure, delivery, and credibility affect journalists’ satisfaction, particularly within local police institutions. This study examines the effectiveness of press release presentations by the Public Relations Division of the Bone Police Department in enhancing journalists’ information satisfaction. Using a quantitative approach, the study surveyed 26 officially registered journalists affiliated with the unit. Data were collected through structured questionnaires and analyzed using simple linear regression. The findings reveal a statistically significant positive correlation between press release effectiveness and journalists’ satisfaction (R² = 0.840, p < 0.05). Key influencing factors include message clarity, source credibility, and digital communication platforms. This study contributes to institutional communication literature by highlighting the strategic role of media relations in shaping the perceived value of public information. It provides practical insights for public sector agencies to refine their communication strategies and build stronger relationships with the media, particularly in regions where accurate and timely information is critical. These findings underscore the importance of professional and credible press releases in improving the flow of public information.